2019
DOI: 10.1177/0091552119850321
|View full text |Cite
|
Sign up to set email alerts
|

A National Study of the Influence of the Community College Pathway on Female Students’ STEM Baccalaureate Success

Abstract: Objective: This study examines the role of community colleges in closing the gender gap in science, technology, engineering, and mathematics (STEM) by studying whether beginning at a community college improves the likelihood of female students earning their bachelor’s degree in STEM. Method: Using nationally representative data, we apply a propensity score matching approach to reduce the selection bias associated with a prospective student’s decision to begin at a community college rather than a 4-year institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Research on the success of women, in general, has found that community colleges provide an intellectually rigorous and comfortable learning environment (Hu & Ortagus, 2019;Jackson & Laanan, 2011;Jackson et al, 2013;Jackson et al, 2013;Perez-Felkner et al, 2019;St. Rose & Hill, 2013;Starobin et al, 2016), where women are more likely to take advantage of student services than men (Miller et al, 2006) and receive more benefit from the learning and advising experience (Packard et al, 2011;Starobin & Laanan, 2008).…”
Section: Community Colleges As Pathways To Stemmentioning
confidence: 99%
“…Research on the success of women, in general, has found that community colleges provide an intellectually rigorous and comfortable learning environment (Hu & Ortagus, 2019;Jackson & Laanan, 2011;Jackson et al, 2013;Jackson et al, 2013;Perez-Felkner et al, 2019;St. Rose & Hill, 2013;Starobin et al, 2016), where women are more likely to take advantage of student services than men (Miller et al, 2006) and receive more benefit from the learning and advising experience (Packard et al, 2011;Starobin & Laanan, 2008).…”
Section: Community Colleges As Pathways To Stemmentioning
confidence: 99%
“…Importantly, students who are able to successfully transfer often see high levels of success. For example, research reveals that attending a community college prior to transfer has no impact on women's STEM bachelor's degree attainment (Hu & Ortagus, 2019). Thus, STEM upward transfer students represent a talented group, and understanding the needs and successes of students who follow degree pathways through community colleges is critical.…”
Section: Community Colleges Are Pivotal To Broadening Participation I...mentioning
confidence: 99%
“…Furthermore, females are inclined not to recognize their success is driven by ability and interest when facing gender stereotypes in subjects (Chen & Suen, 2006). However, studies believed their failure is caused by incompetence and thus enhanced the idea of gender stereotype (Burkley & Blanton, 2007;Huang, 2007;Wang, Chan, Soffa, & Nachman, 2017;Hu & Ortagus, 2019).…”
Section: How Mathematics Impacts Stereotypementioning
confidence: 99%